KORELASI PRESTASI AKADEMIK DAN PRESTASI OLAHRAGA PADA STUDENT-ATHLETE DI UNIVERSITAS PENDIDIKAN INDONESIA - Asrifa Fiorentina Putri, - (2022)
In every university, there must be student-athletes who have their own challenges, namely the heavy training load and the burden of attending classes in class. Thus the student-athletes are required to balance between academic achievement and sports achievement. Therefore, the researcher conducted a study with the aim of knowing whether there was a correlation between academic achievement and sports achievement in student-athletes at the University of Education Indonesia. This research is a correlational study. The method in this study uses descriptive quantitative. The population and sample used in this study were student-athletes in Universitas Pendidikan Indonesia totaled 53 students with a sampling technique using purposive sampling. Analysis of the data between academic achievement and sports achievement found a correlation of 0.696 which means there is a very strong interpretation and positive results. With positive results, the better the value of academic achievement, the better the value of sports achievement. Keyword: student-athletes, academic achievement, sport achievement